Competencies of Health Educators for Sports Injury Prevention - Uspuriene A. B., Simanavičius M. (Science and education: future development, 2020)
according to the analysis of literature, it can be stated in, that there is a lower risk of experiencing sports injury during training, working with such health educators who has higher education in sports science. It is also can be stated that there are few studies which would determine the education of health educators, the quality of training and sports injuries suffered by clients and their frequency during the conducted trainings (Waryasz, Daniels, Gil, Suric, & Eberson, 2016). Research aim – to determine competencies of health educators for sports injury prevention.
Keywords: образование; компетенция; профилактика; преподавание физической культуры; education; competence; prevention; спортивные травмы; sports injuries; health educators